Synthesis of carboxylated chitosan modified with ferromagnetic nanoparticles for adsorptive removal of fluoride, nitrate, and phosphate updates anions from aqueous solutions - Mohammadi, Elham; Daraei, Hiva; Ghanbari, Reza; Athar, Saeed Dehestani; Zandsalimi, Yahya; Ziaee, Amirhosein; Maleki, Afshin; Yetilmezsoy, Kaan (ELSEVIER, 2019)
The present study aimed at synthetizing and preparing carboxylated chitosan adsorbent modified with ferromagnetic nanoparticles and its application to remove nitrate, fluoride, and phosphate anions from aqueous solutions. The properties of synthetized adsorbent were characterized using X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and Dynamic Light Scattering (DLS) methods. To evaluate pH, adsorbent concentration, initial concentration of anions, and contact time, the tests were performed for each anion solely and at the presence of each other. To determine the optimum pH, concentrations of adsorbed anions were evaluated at pH values of 3, 5, and 10, and the results showed higher values in the acidic pH regime. Adsorbent concentration was evaluated at 0.5, 1, 2, 4, 10, and 20 g/L, and results showed higher adsorption rate in higher concentrations. The contact time was also appraised at 10, 30, 60, 90,120, and 150 min, and results indicated that the amount of adsorbed anions by increasing the contact time from 10 to 60 min, while it was remained constant at the contact time above 60 min. Isotherm charts and linear regression coefficient measures demonstrated that the adsorption process was based on the Langmuir model. The kinetics analysis showed that the adsorption process followed Ho and McKay's pseudo-second order type of synthetic reactions. Findings of this study concluded that the modification of chitosan adsorbent could be effectively applied to remove nitrate, fluoride, and phosphate anions from aqueous solutions. (C) 2018 Published by Elsevier B.V.
Keywords: Adsorption; Anion removal; Isotherm; Carboxylated chitosan; Magnetic nanoparticles; WATER; EQUILIBRIUM; PB(II); BIOSORPTION; KINETICS; SORPTION; AS(V); IONS; DYES; Chemistry; Physics